Peripheral Neuropathy Associated with Linezolid Dosage in MDR-TB: A Systematic Review - Muhammad Akbar Ramadhan Munandar; Abdurrachman Machfudz; Hendra Priatna Munandar; Liana Herlina (International Medical Journal Corp. Ltd, 2026)
Introduction: Linezolid is a critical component of modern regimens for multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB). However, its use is limited by significant adverse effects, particularly peripheral neuropathy (PN). The precise relationship between linezolid dosage, treatment duration, and the incidence of PN remains inadequately characterized, posing challenges for optimizing the risk-benefit balance in clinical practice (G. Maartens and C. Benson, 2015). Methods: This comprehensive systematic review analyzed 80 studies, including randomized controlled trials, prospective and retrospective cohorts, systematic reviews with meta-analyses, and case series. Studies were screened and included based on criteria focusing on MDR-TB populations, linezolid use for TB treatment, assessment of PN, provision of dosing details, human subjects, and appropriate study designs. Data were extracted on study characteristics, linezolid dosing regimens, PN incidence and characteristics, other neurological and non-neurological adverse effects, dose-response relationships, patient risk factors, and treatment outcomes (C. Padmapriyadarsini et al., 2022; N. Ahmad et al., 2018). Results: The evidence revealed substantial heterogeneity in linezolid dosing, ranging from 300 mg to 1200 mg daily for durations from weeks to over two years. A clear dose- and duration-dependent relationship with PN was observed. The highest incidence (81%) was reported with 1200 mg/day for 26 weeks, while shorter durations and lower doses (e.g., 600 mg/9 weeks) showed significantly lower rates (13-24%) (F. Conradie et al., 2020; F. Conradie et al., 2022). Structured dose-reduction strategies (e.g., 600 mg to 300 mg) achieved comparable treatment success rates (88-94%) with reduced PN incidence. Other dose-dependent toxicities included myelosuppression and optic neuropathy. Patient risk factors such as diabetes, malnutrition, and alcohol use appeared to modify PN risk (C. Padmapriyadarsini et al., 2024; Yanjun Li et al., 2025). Discussion: The findings underscore that PN risk is influenced by both daily dose and cumulative exposure. The delayed onset (typically after 3 months) suggests a mechanism of cumulative mitochondrial toxicity. While 600 mg daily for 26 weeks offers a favorable balance of efficacy (91% success) and manageable toxicity (24% PN), protocolized dose reduction after an initial intensive phase presents a viable strategy to minimize neurotoxicity while preserving therapeutic effectiveness. The variability in reported PN rates highlights the impact of population-specific risk factors and differences in adverse event monitoring intensity (Xin Zhang et al., 2015; N. Kwak et al., 2025). Conclusion: Peripheral neuropathy is a major, dose- and duration-dependent toxicity of linezolid in MDR-TB treatment. An initial dose of 600 mg daily, with consideration for structured reduction to 300 mg after 9-16 weeks, is supported by evidence as an optimal strategy to maximize efficacy while mitigating neurotoxicity. Active monitoring for PN, especially in patients with underlying risk factors, is essential from 8 weeks of treatment onwards. Future research should focus on therapeutic drug monitoring and personalized dosing strategies to further individualize therapy.